2000
DOI: 10.1111/j.1469-1795.2000.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and palaeontological evidence for the origins of endangered European mink, Mustela lutreola

Abstract: The European mink Mustela lutreola is one of Europe's most endangered carnivores, with few vulnerable populations remaining. Surprisingly, a recent phylogeny placed a single mink specimen within the polecat (M. putorius, M. eversmannii) group, suggesting a recent speciation and/or the effects of hybridization. The analysis has now been extended to a further 51 mink and polecats. As before, phylogenetic methods failed to resolve the relationships between the species. One haplotype (C11) was found in both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 30 publications
(26 reference statements)
9
59
0
Order By: Relevance
“…Mitochondrial studies have suggested that European mink is most closely related to the polecat (Mustela putorius) or to the steppe polecat (Mustela eversmanni), though the similarity may be a consequence of hybridization, in the late Pleistocene or Holocene (Davison et al, 2000). A nuclear DNA study seems to confirm this (Sato et al in press).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Mitochondrial studies have suggested that European mink is most closely related to the polecat (Mustela putorius) or to the steppe polecat (Mustela eversmanni), though the similarity may be a consequence of hybridization, in the late Pleistocene or Holocene (Davison et al, 2000). A nuclear DNA study seems to confirm this (Sato et al in press).…”
Section: Introductionsupporting
confidence: 59%
“…In fact, it is possible that European mink were never distributed across most of western Europe during the Holocene. The fossil record is sparse (Davison et al, 2000), with the only confirmed records being an undated, probably Holocene, skull from Moscow District, another Holocene specimen from the Netherlands, material from the Polish site of Biskupin, and from the Romanian site of the 'La Adam' Cave (references in Davison et al, 2000). Although there is no direct evidence, there has also been some debate as to whether the western population is a recent introduction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EFSA reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Davison et al, 2000;Lode, Guiral & Peltier, 2005). The domestic ferret (Mustela furo) can hybridise with the polecat (Mustela putorius), which is recorded across most of Europe (Davison et al, 2001).…”
Section: Defining Environmental Risk Assessment Criteria For Geneticamentioning
confidence: 99%